Predicting Early Childhood Readiness to Enter Elementary School Using the Naive Bayes Classification - Puspitorini, Sukma; Kahar, Novhirtamely; Kartika, Ikah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to examine the readiness and maturity of early childhood in entering elementary school using the Naïve Bayes method. This analysis involves variables such as gender, age, aspects of physical-motor, cognitive, social-emotional development, and literacy skills which include reading, writing, arithmetic, and children's level of independence. The readiness category is classified into two classes, namely